Characteristics of the surface water DMS and pCO2 distributions and their relationships in the Southern Ocean, southeast Indian Ocean, and northwest Pacific Ocean. Issue 8 (26th August 2017) - Zhang, Miming; Marandino, C. A.; Chen, Liqi; Sun, Heng; Gao, Zhongyong; Park, Keyhong; Kim, Intae; Yang, Bo; Zhu, Tingting; Yan, Jinpei; Wang, Jianjun
Abstract: Oceanic dimethyl sulfide (DMS) is of interest due to its critical influence on atmospheric sulfur compounds in the marine atmosphere and its hypothesized significant role in global climate. High‐resolution shipboard underway measurements of surface seawater DMS and the partial pressure of carbon dioxide ( p CO2 ) were conducted in the Atlantic Ocean and Indian Ocean sectors of the Southern Ocean (SO), the southeast Indian Ocean, and the northwest Pacific Ocean from February to April 2014 during the 30th Chinese Antarctic Research Expedition. The SO, particularly in the region south of 58°S, had the highest mean surface seawater DMS concentration of 4.1 ± 8.3 nM (ranged from 0.1 to 73.2 nM) and lowest mean seawater p CO2 level of 337 ± 50 μatm (ranged from 221 to 411 μatm) over the entire cruise. Significant variations of surface seawater DMS and p CO2 in the seasonal ice zone (SIZ) of SO were observed, which are mainly controlled by biological process and sea ice activity. We found a significant negative relationship between DMS and p CO2 in the SO SIZ using 0.1° resolution, [DMS]seawater  = −0.160 [ p CO2 ]seawater  + 61.3 ( r 2  = 0.594, n  = 924, p  < 0.001). We anticipate that the relationship may possibly be utilized to reconstruct the surface seawater DMS climatology in the SO SIZ. Further studies are necessary to improve the universality of this approach. Key Points: The characteristics of surface water DMS and p CO2 distributions from the Southern Ocean to northwest Pacific Ocean are investigated The correlations between DMS, p CO2, and environmental parameters are analyzed Anticorrelation between DMS and p CO2 is found in the seasonal ice zone of the Southern Ocean